Adequacy of antenatal steroids, rather than place of birth, determines survival to discharge in extreme prematurity in North Queensland. (27th August 2018) - Ireland, Susan; Larkins, Sarah; Ray, Robin; Woodward, Lynn; Devine, Kirsty
Abstract : Aim: The Townsville Hospital cares for babies in a large geographical area, many of who are outborn, are of Aboriginal or Torres Strait Islander origin and have families who reside in areas of deprivation. This study examined the outcomes of babies born at all locations in North Queensland to assess the predictors of poor outcomes. Methods: A retrospective observational study examined the survival of 313 babies born from 22 completed weeks gestation to 27 + 6 weeks gestation in North Queensland between January 2010 and December 2016. Additional analyses were performed for the 300 non‐syndromal babies whose mothers usually resided in North Queensland, studying demographics of gestation, gender, birthweight, Indigenous status, regionality of maternal residence and adequacy of antenatal steroids. Short‐term morbidities of intraventricular haemorrhage/periventricular leukomalacia (IVH/PVL), surgical necrotizing enterocolitis, retinopathy of prematurity requiring treatment and chronic lung disease and death were studied in relation to demographic factors and clinical treatment. Results: Adequacy of steroids was significantly associated with a decreased mortality odds ratio of 2.872 (95% confidence interval 1.228–6.715), whilst no difference in outcome was seen by retrieval status or ethnic origin. Babies from remote locations were at increased risk for IVH/PVL, 2.334 (1.037–5.255). Male babies suffered more chronic lung disease, 1.608 (1.010–2.561), and IVH/PVL, 2.572 (1.215–5.445). Aboriginal and Torres Strait Islander babies were at lower risk of IVH/PVL. Conclusions: Steroids should be administered wherever there is any possibility of the provision of intensive care for periviable babies. Place of birth and ethnicity of mother should not unduly influence antenatal counselling.